2002
DOI: 10.1016/s0002-9440(10)61136-4
|View full text |Cite
|
Sign up to set email alerts
|

ADAM 12 Protease Induces Adipogenesis in Transgenic Mice

Abstract: ADAM 12 (meltrin-alpha) is a member of the ADAM (a disintegrin and metalloprotease) family. ADAM 12 functions as an active metalloprotease, supports cell adhesion, and has been implicated in myoblast differentiation and fusion. Human ADAM 12 exists in two forms: the prototype membrane-anchored protein, ADAM 12-L, and a shorter secreted form, ADAM 12-S. Here we report the occurrence of adipocytes in the skeletal muscle of transgenic mice in which overexpression of either form is driven by the muscle creatine ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 33 publications
5
75
0
1
Order By: Relevance
“…Previously, our laboratory reported that activated PAR-1 led to cardiac remodeling (21) and that inhibition of MMPs prevented connexin-43 degradation and ameliorated heart failure (13). In the present study, we found that, other than increased expression of PAR-1, ADAM-12, an enzyme involved in cell adhesion and myoblast differentiation and fusion (15), was also overexpressed in AVF animals. This finding suggests that increased activity of PAR-1 could lead to activation of several proteolytic events.…”
Section: Discussionsupporting
confidence: 66%
“…Previously, our laboratory reported that activated PAR-1 led to cardiac remodeling (21) and that inhibition of MMPs prevented connexin-43 degradation and ameliorated heart failure (13). In the present study, we found that, other than increased expression of PAR-1, ADAM-12, an enzyme involved in cell adhesion and myoblast differentiation and fusion (15), was also overexpressed in AVF animals. This finding suggests that increased activity of PAR-1 could lead to activation of several proteolytic events.…”
Section: Discussionsupporting
confidence: 66%
“…Alternatively, TIMP-3 suppression might influence the activity of the ADAM (a disintegrin and metalloprotease) family of metalloproteinases because reports indicated that TIMP-3 exhibits inhibitory activity against several ADAMs that are not inhibited by other TIMPs, such as tumor necrosis factor ␣ convertase (ADAM-17) (7,36). In support of this, Kawaguchi et al (40) recently found that female transgenic mice expressing ADAM-12 become obese, demonstrating that an ADAM metalloproteinase might also regulate adipogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…The complex but conserved structure of ADAM family members endows these proteins with various abilities leading to their key contribution to various physiological functions such as, for instance, fertilization [15,32], neurogenesis [33], adipogenesis [34,35] and myogenesis [36]. ADAMs and ADAMTSs are involved in a complex molecular network of reciprocal interactions.…”
Section: Implication Of Adams and Adamtss In Physiology And Pathologymentioning
confidence: 99%